France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes expenditure reforms in France. After decades of rising public spending and successive tax increases, the medium-term fiscal consolidation path described in the 2015 Stability Program is now fully expenditure based. However, recent efforts of nominal spending containment have not delivered the intended savings in the context of low growth and inflation. A thorough review of the efficiency of public spending could help prepare more fundamental reforms of spending programs and processes to underpin a lasting reduction in expenditures, which reached a record high of 57.2 percent of GDP in 2014.